DETERMINANTS OF HUMAN RESOURCE MANAGEMENT IN HEALTH CARE INSTITUTIONS - UCIEKLAK-JEŻ Paulina; BEM Agnieszka (2017)
The aim of the paper is to present specific conditioning of a personal function in health care's institutions, hospitals in the first place. Detailed hypotheses have been formulated as follow: · there are specific legal determinants of human resource management in health care units, · there are specific demographic determinants of human resource management in health care units, · there are specific economic determinants of human resource management in health care units. Research carried out in this area clearly indicate, that the approach to the personal function is different in hospitals that have undergone a restructuring process and in hospitals that haven't launched any restructuring program.